Strain relaxation in convex-graded InxAl1-xAs (x = 0.05–0.79) metamorphic buffer layers grown by molecular beam epitaxy on GaAs(001). (January 2018) - Solov'ev, V.A.; Chernov, M. Yu; Baidakova, M.V.; Kirilenko, D.A.; Yagovkina, M.A.; Sitnikova, A.A.; Komissarova, T.A.; Kop'ev, P.S.; Ivanov, S.V.
Abstract: This paper presents a study of structural properties of InGaAs/InAlAs quantum well (QW) heterostructures with convex-graded Inx Al1-x As ( x = 0.05–0.79) metamorphic buffer layers (MBLs) grown by molecular beam epitaxy on GaAs substrates. Mechanisms of elastic strain relaxation in the convex-graded MBLs were studied by the X-ray reciprocal space mapping combined with the data of spatially-resolved selected area electron diffraction implemented in a transmission electron microscope. The strain relaxation degree was approximated for the structures with different values of an In step-back. Strong contribution of the strain relaxation via lattice tilt in addition to the formation of the misfit dislocations has been observed for the convex-graded InAlAs MBL, which results in a reduced threading dislocation density in the QW region as compared to a linear-graded MBL. Highlights: Convex-graded InAlAs metamorphic buffer is employed to grow In0.75 Ga0.25 As QW on GaAs. Strain relaxation in the InAlAs buffers with In content up to 79 mol. % is studied. X-ray reciprocal space mapping and selected area electron diffraction are used. Lattice tilt contributes strongly to strain relaxation in the convex-graded buffer. Reduced threading dislocation density in QW region is inherent for the tilted buffers.